2014
DOI: 10.3109/00365521.2014.909528
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic radiation force impulse elastography and serum fibrosis markers in chronic hepatitis C

Abstract: ARFI elastography had very good accuracy for the assessment of liver fibrosis. It was more effective than APRI, Forns, King, and FIB-4 scores for the prediction of significant fibrosis and cirrhosis in CHC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Many researchers have reported that liver stiffness correlated with liver fibrosis stage, and ARFI increased as the fibrosis stage increased . Before our study, the reported ARFI cut‐off ranges were 1.2–1.35 m/s for ≥F2, 1.54–1.7 m/s for ≥F3, and 1.74–2.0 m/s for F4 .…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Many researchers have reported that liver stiffness correlated with liver fibrosis stage, and ARFI increased as the fibrosis stage increased . Before our study, the reported ARFI cut‐off ranges were 1.2–1.35 m/s for ≥F2, 1.54–1.7 m/s for ≥F3, and 1.74–2.0 m/s for F4 .…”
Section: Discussionmentioning
confidence: 62%
“…Silva Junior et al . reported that ARFI was more accurate than APRI, Forns score, King's score, and the FIB‐4 index in 51 hepatitis C patients . Fierbinteanu‐Braticevici et al .…”
Section: Discussionmentioning
confidence: 99%
“…Our study adds on previous reports demonstrating that, in addition to TE, shear‐wave and other similar techniques may efficiently assess LS in patients with CLD of different aetiology . Such techniques include point shear‐wave elastography quantification (such as ElastPQ) and shear‐wave quantification techniques, all showing the advantage over TE of being implemented on a regular US equipment and allowing multiple LS measurements on the direct visualisation of the anatomical structures.…”
Section: Discussionmentioning
confidence: 63%
“…Silva Junior et al performed a prospective study comparing the use of ARFI, the FIB‐4, and the Forns and Kings scores in hepatitis C and found that the ARFI was more useful than other serum indicators for predicting liver fibrosis and cirrhosis. However, in this study, ARFI was equally as useful as the APRI and was more useful than the FIB‐4 for assessing substantial liver fibrosis in hepatitis B.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have affirmed that the SWV, aspartate aminotransaminase‐to‐platelet ratio index (APRI), and fibrosis‐4 index (FIB‐4) have positive significance in predicting the liver fibrosis stage of viral hepatitis B or C . Currently, only a few studies have compared the value of the SWV, APRI, and FIB‐4 in the diagnosis of liver fibrosis caused by chronic hepatitis C or B; therefore, it is a dilemma for physicians to select the best tests among the SWV, APRI, FIB‐4, aspartate aminotransferase‐to‐alanine aminotransferase ratio (AAR), and their combinations. This retrospective study aimed to analyze the values of the SWV, APRI, FIB‐4, AAR, and their combinations in predicting the stage of liver fibrosis caused by chronic hepatitis B.…”
mentioning
confidence: 99%